Applying Public Health Screening Criteria: How Does Universal Newborn Screening Compare to Universal Tumor Screening for Lynch Syndrome in Adults with Colorectal Cancer?. Issue 3 (18th October 2014) - Cragun, Deborah; DeBate, Rita D.; Pal, Tuya
Abstract: Institutions have increasingly begun to adopt universal tumor screening (UTS) programs whereby tumors from all newly diagnosed patients with colorectal cancer (CRC) are screened to identify who should be offered germline testing for Lynch syndrome (the most common cause of hereditary CRC). Given limited information about the impact of universal screening programs to detect hereditary disease in adults, we apply criteria used to evaluate public health screening programs and compare and contrast UTS with universal newborn screening (NBS) for the purpose of examining ethical implications and anticipating potential outcomes of UTS. Both UTS and a core set of NBS conditions clearly meet most of the Wilson and Jungner screening criteria. However, many state NBS panels include additional conditions that do not meet several of these criteria, and there is currently insufficient data to confirm that UTS meets some of these criteria. Comparing UTS and NBS with regard to newer screening criteria raises additional issues that require attention for both UTS and NBS. Comparisons also highlight the importance of evaluating the implementation of genomic tests to ensure or improve their effectiveness at reducing morbidity and mortality while minimizing potential harms.